Экстракционно-абсорбциометрическое определение меди бриллиантовым зеленым в вине и коньяке - Мангасарян, Сирвард
Interaction of cupric chloride anionic complex with threephenylmethane basic dye – brilliant green has been studied. The colored ionic associate is extracted by dichlorethane:toluol (1:4) binary mixture out of pH2 HCl solution. The method is based on the reduction of copper (II) to copper (I) with ascorbic acid. The calibration graph obeyed Beer’s law over the range 0,142-2,5 mkg/ml copper and the apparent molar absorptivity of the extract at 625 nm was 1.215 105 l mol-1cm-1. The molar ratio between copper (I) chloride complex and brilliant green in ionic associate has been determined by Asmuse straight line and shifts of equilibrium methods, which (1:1). The influence of interfering elements on the determination of copper has been studied. The elaborated methods have been applied for the determination of copper in wine and gognac. The proposed method is very sensitive and simple than those reported earlier.
Keywords: Аналитическая химия